2018
DOI: 10.22587/anas.2018.12.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation distribution and ecological risk assessment of some trace metals in artificial estuary: Vridi channel (Côte d'Ivoire)

Abstract: BACKGROUND: The modified of Community Bureau of Reference (modified BCR) sequential extraction procedure has been one of common methods used for the trace metals speciation in sediments and allowed to the assessment of the ecological risk state of aquatic ecosystem based on ecological risk indexes. OBJECTIVE: The modified BCR sequential extraction procedure was used to the fractionation distribution of Cd, Co, Cu, Ni, Pb and Zn in sediment samples of Vridi channel, and three ecological indexes based on this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Given its position, the water seasons of this estuary result from those of Atlantic Ocean in front of Abidjan district defined by Durand and Skibich [13] and those of Ébrié system defined by Durand and Guiral [14]. Yao and Trokourey [10,15] and Yao et al [16] define them as follow:…”
Section: Fig 1 Geographical Location Of Vridi Channelmentioning
confidence: 99%
See 3 more Smart Citations
“…Given its position, the water seasons of this estuary result from those of Atlantic Ocean in front of Abidjan district defined by Durand and Skibich [13] and those of Ébrié system defined by Durand and Guiral [14]. Yao and Trokourey [10,15] and Yao et al [16] define them as follow:…”
Section: Fig 1 Geographical Location Of Vridi Channelmentioning
confidence: 99%
“…This fact is the consequence of the dysfunction and obsolescence of the sanitation system in Abidjan district [19]. Also, this estuary is also the transit point for many pollutants carried by continental waters in Atlantic Ocean in general, and in particular those by the coastal rivers Agnéby and Mé, and from the Comoé river [16,10,15]. This is due to the development and intensification of agriculture with intensive use of phytosanitary products in their watersheds.…”
Section: Fig 1 Geographical Location Of Vridi Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…This biodiversity is highly threatened by strong anthropogenic pressures. For illustration, the studies carried out by Yao et al [30] and Yao et Trokourey [31,32] in its former hydromorphology showed a relatively high pollution of its surperfcial sediments by trace metals. This is also the case with those of Konan et al [33] who highlighted a relatively high pollution of these substrates by polycyclic aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%